Involvement of Circulating Exosomal MicroRNAs in Jian-Pi-Yi-Shen Formula Protection Against Adenine-Induced Chronic Kidney Disease - Xinhui Liu; Siqi Liu; Denggui Luo; Shiying Huang; Fochang Wang; Bing Zhang; Yulian Chen; Lin Zheng; Jiandong Lu; Shunmin Li (Frontiers in Pharmacology, 2021)
Jian-Pi-Yi-Shen formula (JPYSF) is a traditional Chinese medicine (TCM) formula used in clinic to treat chronic kidney disease (CKD) for decades. However, the mechanisms of JPYSF in treating CKD have not been fully elucidated. The aim of the present study was to test the renoprotective effect of JPYSF on CKD rat model and investigate the potential mechanism from the perspective of serum exosomal microRNAs (miRNAs). CKD rat model was induced by feeding Sprague-Dawley rats a diet containing 0.75% w/w adenine for four weeks. The rats in the treatment group were given 10.89 g/kg JPYSF by gavage every day, starting from the 3rd week of the adenine-containing diet for six weeks. Serum biochemistry and histopathology were used to evaluate the renoprotective effects of JPYSF. Serum exosomes were isolated by ExoQuick-TC PLUS exosomes extraction kit and were identified by transmission electron microscopy, nanoparticle tracking analysis, and western blot. Exosomal miRNAs profiling was analyzed by small RNA sequencing. The results showed that JPYSF treatment significantly lowered serum creatinine and blood urea nitrogen levels and alleviated renal pathological injury in CKD rats. Furthermore, serum exosomes were successfully isolated and identified. Small RNA sequencing revealed that 4 exosomal miRNAs (miR-192-5p, miR-194-5p, miR-802-5p, and miR-143-3p) were significantly downregulated in the CKD group and were markedly upregulated after JPYSF treatment. At last, miR-192-5p was identified as the most relevant miRNA for CKD diagnosis and JPYSF treatment. In conclusion, JPYSF protects kidney from adenine-induced CKD, which may be associated with modulation of exosomal miRNAs.